Sustainable Development Goals 1 & 2 Compliant: Evaluating Nigeria’s Agricultural Policies 2010 - 2019 - Egberi, Anthony Ejue (iRASD Journal of Management, 2023)
The study focuses on Nigeria's agriculture policies and their alignment with the Sustainable Development Goals (SDGs) 1 and 2. It examined historical and present agricultural policies, food security, and their compliance or relevance to the United Nations set goals or policy framework of Sustainable Development Goals 1 and 2. According to the document, despite the Nigerian government's laws and programs, there is still a severe threat of food insecurity to the Nigerian cooperative's existence. In this context, it was investigated to what extent the Nigerian economy is in sync or accord with the idea of the Sustainable Development Goals 1 and 2 and agricultural and food security plans. It questioned and investigated the capacity of the Nigerian economy's structural features to impede or assist the realization of food security under Sustainable Development Goal 1&2. As a result, the study detailed and analyzed the agricultural aims, concepts, and programs of the Sustainable Development Goals 1 and 2. It also looked at the structure of the Nigerian economy concerning its output structure, domestic economic capacity, and social structure capacity in the context of SDGs 1 and 2 agriculture and food security objectives. Furthermore, it x-rayed the requirements for compliance. Finally, it concluded and made some policy recommendations.